India : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for India. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights strong growth recorded by the Indian economy in recent years helped by a large terms-of-trade gain and positive policy actions. Inflation has remained low following the collapse in global commodity prices, a range of supply-side measures, and a relatively tight monetary stance. Fiscal consolidation at the Union Government level resumed in FY2016/17 and has been complemented by measures to enhance the quality of public spending. Growth is projected to slow to 6.6 percent in FY2016/17 and then rebound to 7.2 percent in FY2017/18, owing to temporary disruptions, primarily to private consumption, caused by cash shortages.